Eggplant grafting on a cold-tolerant rootstock reduces fruit chilling susceptibility and improves antioxidant stability during storage - Darré, Magalí (2021)
BACKGROUND: Vegetable grafting has been increasingly evaluated to improve preharvest tolerance to biotic and abiotic stresses. However, very few studies have identified rootstock–scion combinations able to improve fruit shelf life and reduce the susceptibility to postharvest disorders. Herein, a purple eggplant scion (cv. Monarca) was grafted onto a cold-tolerant hybrid Solanum rootstock (‘Java’) and the changes in growth, quality, postharvest chilling tolerance, and antioxidant stability were evaluated. RESULTS: Eggplant grafting enhanced plant vigor and fruit growth rate, decreasing the time from set to harvest by 10–15%. Grafted eggplants had a thinner shape and lighter pulp color than the control. The rootstock–scion combination tested showed lower respiration (~60%), dry matter (~15–20%), and phenolic compounds contents (~15–20%) than eggplants from non-grafted plants. Grafting markedly improved fruit performance during postharvest storage. Remarkably, grafted eggplants showed much higher tolerance to chilling injury than the control did, evidenced by a reduction of surface scalds along with decreased softening and pulp browning. The trend in antioxidants found at harvest time was reversed after cold storage due to enhanced stability (20% and 100% for pulp and peel respectively) in fruit from grafted plants. CONCLUSION: Purple eggplant (cv. Monarca) grafting onto ‘Java’ hybrid rootstock modulated fruit growth, quality at harvest, and increased fruit chilling injury tolerance during storage. Grafting may be a bona fide strategy to induce phenotypic traits able to improve vegetable postharvest performance.